Faking the News: Intentional Guided Variation Reflects Cognitive Biases in Transmission Chains Without Recall. Issue 1 (10th October 2018) - Stubbersfield, Joseph; Tehrani, Jamshid; Flynn, Emma
Two potential forms of mutation in cultural evolution have been identified: 'copying error', where learners make random modifications to a behaviour and 'guided variation' where learners makes non-random modifications. While copying error is directly analogous to genetic mutation, guided variation is a specifically cultural process that does not have a close parallel in biological evolution. It has been suggested that the decision-making processes underlying intentional guided variation may produce similar results to cultural transmission as both are likely to be influenced by cognitive biases. This study uses a unique linear transmission chain design, without any influence of recall, to examine intentional guided variation. Participants were asked to alter news stories however they wished in order to make them more interesting, the product of their modification was then passed to the next participant and so on down the chain. The products of the chains were then compared with the original material so as to assess any underlying biases in the changed content. Through this process of guided variation, original material which scored low for bias-exploiting content significantly increased in at least one known content bias, whereas original material which scored high for bias-exploiting content was not significantly altered in this respect.